The expositor's Bible commentary ; v. 8 - Gaebelein, Frank Ely 1899-1983; Carson, Don A.; Wessell, Walter W.; Liefeld, Walter L. (Grand Rapids, MI : Zondervan, 1984)
Contents : v. 8 : Matthew / D.A. Carson; Mark / Walter W. Wessell; Luke / Walter L. Liefeld
Contents : Matthew / D.A. Carson -- Mark / Walter W. Wessel - Luke / Walter L. Liefeld.
Includes bibliographical references and indexes.
Keywords: Bible. -- commentaries; Bible. -- commentaries; Bible. -- commentaries